Strongly Correlated Alignment of Fluorinated 5, 11‐Bis(triethylgermylethynyl)anthradithiophene Crystallites in Solution‐Processed Field‐Effect Transistors. Issue 14 (8th August 2014) - Kim, Chang‐Hyun; Hlaing, Htay; Payne, Marcia M.; Yager, Kevin G.; Bonnassieux, Yvan; Horowitz, Gilles; Anthony, John E.; Kymissis, Ioannis
Abstract The crystallinity of an organic semiconductor film determines the efficiency of charge transport in electronic devices. This report presents a micro‐to‐nanoscale investigation on the crystal growth of fluorinated 5, 11‐bis(triethylgermylethynyl)anthradithiophene (diF‐TEG‐ADT) and its implication for the electrical behavior of organic field‐effect transistors (OFETs). diF‐TEG‐ADT exhibits remarkable self‐assembly through spin‐cast preparation, with highly aligned edge‐on stacking creating a fast hole‐conducting channel for OFETs.